Characteristics of pressure injuries among geriatric patients at an Indonesian tertiary hospital: a cross-sectional study - Yusharyahya, Shannaz Nadia; Legiawati, Lili; Astriningrum, Rinadewi; Jonlean, Reganedgary; Andhira, Vega (Faculty of Medicine Universitas Indonesia, 2023)
BACKGROUND Pressure injury develops due to sustained pressure at the bony prominence of the skin and tissues. Geriatric patients often have multiple comorbidities, predisposing them to pressure injury. Data on the characteristics of the geriatric with pressure injuries are still limited. This study aimed to report the characteristics of geriatric patients with pressure injuries admitted at a tertiary hospital in Indonesia. METHODS This cross-sectional study used medical records of geriatric patients admitted with all stages of pressure injuries consulted to the Department of Dermatology and Venereology at a tertiary hospital in Indonesia between January 2017 and April 2021. Pressure injuries were classified based on the 2019 National Pressure Injury Advisory Panel guideline. RESULTS 39 patients presented with varied pressure injury characteristics. The sacral region was the most reported site (36%), with stage 2 pressure injury being the most commonly found stage in the patients (74%). Interestingly, 22% of the patients had pressure injuries found on the atypical sites due to prolonged surgery or the pressure of medical devices. More than half of the patients used conventional dressings (51.3%). Immobility was found in 35.9% of the patients due to being bedridden. CONCLUSIONS No characteristics were found as a significant risk factor for pressure injury formation during or outside the admission period. However, a history of surgery might be related to pressure injury formation during admission.